Forgiveness Therapy to Improve Subjective Well-Being Among Families of Patients with Chronic Illness - Diana, Raden Rachmy; Nashori, Fuad; Pihasniwati, Pihasniwati; Indranata, Asiska Danim; Fitri, Rahma Kusuma (Universitas Muhammadiyah Yogyakarta, 2023)
Families (caregivers) of patients with chronic illness should ideally have high subjective well-being to care for chronic illness patients well. In reality, they cry frequently, look pensive, and have difficulty carrying out daily activities. This quasi-experimental study aims to examine the effect of forgiveness therapy on increasing the subjective well-being of families (caregivers) of patients with chronic illness. There were 11 participants (3 males and 9 females) divided into two groups, i.e., the treatment group consisting of 6 persons (1 male and 5 females) and the control group consisting of 5 persons (2 males and 3 females) who have looked after the patients with chronic illness for 2–8 years. The subjective well-being was measured by the Satisfaction with Life Scale (SWLS) and the Positive Affect Negative Affect Schedule (PANAS). The data were then analyzed using Mann-Whitney to compare means. The results showed differences in subjective well-being between the treatment and control groups. The results showed that forgiveness therapy has effectively improved subjective well-being in families or patients with chronic illness. Based on the results, the researcher suggested that forgiveness therapy can be used to provide psychological interventions to families of patients with chronic illnesses. Families still need support to optimize and stabilize the patient’s health condition